Formulation and in vitro evaluation of mucoadhesive controlled release matrix tablets of flurbiprofen using response surface methodology - Ikrima Khalid; Mahmood Ahmad; Muhammad Usman Minhas; Muhammad Sohail (Universidade de São Paulo, 2014)
The objective of the current study was to formulate mucoadhesive controlled release matrix tablets of flurbiprofen and to optimize its drug release profile and bioadhesion using response surface methodology. Tablets were prepared via a direct compression technique and evaluated for in vitro dissolution parameters and bioadhesive strength. A central composite design for two factors at five levels each was employed for the study. Carbopol 934 and sodium carboxymethylcellulose were taken as independent variables. Fourier transform infrared (FTIR) spectroscopy studies were performed to observe the stability of the drug during direct compression and to check for a drug-polymer interaction. Various kinetic models were applied to evaluate drug release from the polymers. Contour and response surface plots were also drawn to portray the relationship between the independent and response variables. Mucoadhesive tablets of flurbiprofen exhibited non-Fickian drug release kinetics extending towards zero-order, with some formulations (F3, F8, and F9) reaching super case II transport, as the value of the release rate exponent (n) varied between 0.584 and 1.104. Polynomial mathematical models, generated for various response variables, were found to be statistically significant (P<0.05). The study also helped to find the drug's optimum formulation with excellent bioadhesive strength. Suitable combinations of two polymers provided adequate release profile, while carbopol 934 produced more bioadhesion.